Ecological Relationship between Poverty and Nutritional Status of Toddler in Indonesia in 2018 - Wasis Budiarto; Ratna Dwi Wulandari; Nikmatur Rohmah; Agung Dwi Laksono (Indian Journal of Forensic Medicine & Toxicology, 2021)
Data in the world states that 462 million are underweight, 47 million children under the age of 5 are wasting,14.3 million are very thin, and 144 million are stunting. Previous study reports about 45% of child deaths<5 years are related to malnutrition—the study aim to analyzing the relationship between poverty andnutritional status of the toddler in Indonesia ecologically. The study used secondary data from the officialreport of the Indonesia Ministry of Health. The study takes all provinces as samples. Moreover, the studyused the percentage of poor people as an independent variable. On the other hand, the researchers analyzedthree other variables as dependent variables: the proportion of underweight toddlers, the proportion ofstunting toddlers, and the proportion of wasting toddlers. The study examined the data using a scatter plot todetermine the relationship. The results show that the greater the percentage of an underweight toddler in acountry, the higher the proportion of underweight toddler in that region. Meanwhile, the more significant theproportion of the deprived population in an area, the more considerable proportion of stunting in that area.Moreover, the higher the poor people in the province, the higher the proportion of wasting in that province.The study concluded that poverty has a relationship with nutrition status of the toddler in Indonesia.